2011
DOI: 10.1227/neu.0b013e31821bc49c
|View full text |Cite
|
Sign up to set email alerts
|

Thromboembolic Complications After Neuroform Stent-Assisted Treatment of Cerebral Aneurysms: The Duke Cerebrovascular Center Experience in 235 Patients With 274 Stents

Abstract: Our results suggest that the thromboembolic event rate associated with Neuroform stent use is low in unruptured aneurysms. In ruptured aneurysms, the complication rate is high, possibly partly related to restricted use of antiplatelet therapy. Stent size and hypertension may be associated with the risk of stroke, but additional studies are needed to confirm their significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
41
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 28 publications
3
41
1
Order By: Relevance
“…Recently, a case series of 284 patients harboring 302 aneurysms treated by stent-assisted coiling with the Neuroform stent reported an 8.8% incidence of ischemic strokes. 34 The delayed thromboembolic event rate in SENAT (3%) is similar to previous studies 5,11,25,33 ranging between 3.5% and 6.6%. Among the 3 patients in SENAT, 1 case was concomitant to the cessation of dual antiplatelet therapy after stent placement.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Recently, a case series of 284 patients harboring 302 aneurysms treated by stent-assisted coiling with the Neuroform stent reported an 8.8% incidence of ischemic strokes. 34 The delayed thromboembolic event rate in SENAT (3%) is similar to previous studies 5,11,25,33 ranging between 3.5% and 6.6%. Among the 3 patients in SENAT, 1 case was concomitant to the cessation of dual antiplatelet therapy after stent placement.…”
Section: Discussionsupporting
confidence: 86%
“…The occurrence of periprocedural thromboembolic events was low (3.7%) and compares favorably with the literature (4.5%-21%). 5,8,32 As shown by Lessne et al, 33 the thromboembolic rates for ruptured aneurysms and UIAs, treated by stent-assisted coiling, are very different (20% and 3.1%, respectively). This wide range could be explained by the lack of standardized antiplatelet regimen among centers.…”
Section: Discussionmentioning
confidence: 93%
“…Similar to our results, they reported that stent insertion for acutely ruptured aneurysms is associated with higher thromboembolic and hemorrhagic complications than stent insertion for unruptured aneurysms (25% vs 4.7%). Additionally, Lessne et al 22 reported thromboembolic complications after Neuroform stent-assisted treatment of cerebral aneurysms in 235 patients with 274 stents. There were 6 (3.1%) thromboembolisms in 194 patients with unruptured aneurysms and 6 (20%) among 30 patients with ruptured aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with intracerebral lesions, a major surgical complication is the high incidence of thromboembolic events, 17 including life-threatening pulmonary embolisms. 15 Lessne et al 22 showed that acute SAH before stent placement proved to be a risk factor for subsequent thromboembolic events. Cronqvist et al…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation